In vitro diagnosis of resistance of the cattle tick Rhipicephalus (Boophilus) microplus to fipronil in Argentina - Torrents, Jorgelina (2020)
The aim of this work was to adapt and apply the in vitro larval bioassay packet test (LPT) to diagnose resistance of Rhipicephalus microplus ticks to fipronil in Argentina. Ten serial dilutions of fipronil were included in the LPT bioassay. Seven populations of R. microplus from six Argentinean Provinces were evaluated. Samples from Colonia Benítez, Quimilí and Intiyaco were unambiguously classified in the category ‘resistant’. In all these cases the 95% confidence intervals did not overlap with that of the susceptible reference strain and the slope values were lower than the slope value obtained for the susceptible reference strain. The resistance ratio (RR50) values of the populations from Colonia Benítez I and II, Quimilí and Intiyaco were 2.23, 3.49, 6.84 and 3.39, respectively. Populations from El Colorado I and II, Acambuco, Vera and Feliciano were classified as ‘susceptible’ because the 95% confidence intervals overlapped with that of the susceptible reference strain and the RR50 values never exceeded 1.32. The results of these LPT bioassays indicate the presence of fipronil resistant R. microplus populations in Argentina.